Optimización del proceso de extracción hidroalcohólica a partir de la guayusa (Ilex guayusa loes) en función del contenido de polifenoles totales y actividad antioxidante - Granja Guerrero, Darwin Vicente (2022)
The present investigation was carried out with the objective of optimizing the hydroalcoholic extraction process through the maceration of the raw substance of the guayusa leaf, after being subjected to a cleaning process, to then be dehydrated in an oven at 40ºC. . The factors tested were time (6h, 15h, 24h), temperature (30°C, 45°C, 60°C), and ethanol concentration (60%, 75%, 90%); in the extraction, 27 repetitions were made, established by the Desig Expert 8.0.6 program. Next, the secondary metabolites were determined through the phytochemical profile, evidencing in the ethanolic and aqueous extract a greater amount of phenolic compounds and flavonoids. Total polyphenol content was evaluated according to the FOLIN technique described by Slinkard and Sigleton. The antioxidant capacity was determined through the FRAP procedure proposed by Benzie and Strain. For the numerical optimization, it was found that the values achieved through experimentation (total polyphenols 420.452mg/g and 1124.56 µmol Fe2+/g of antioxidant capacity) are higher than the values of the numerical optimization provided by the software (408.452g/g and 1099. 56 µmol Fe2+/ g), the extract had a characteristic aroma of the plant, dark green in color, with a uniform and homogeneous appearance at a pH of 5.